1997
DOI: 10.2337/diab.46.6.941
|View full text |Cite
|
Sign up to set email alerts
|

B-Cells Are Required for the Initiation of Insulitis and Sialitis in Nonobese Diabetic Mice

Abstract: Nonobese diabetic (NOD) mice spontaneously develop an acute onset of hyperglycemia reminiscent of human type I diabetes. The disease is the end result of a mononuclear cell infiltration of pancreatic islets (insulitis), culminating in the selective destruction of islet beta-cells by autoreactive T-cells. NOD mice also exhibit defects in B-cell tolerance as manifested by the presence of autoantibodies against islet cell autoantigens. Based on the potential ability of B-cells to act as antigen presenting cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
161
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 0 publications
8
161
0
2
Order By: Relevance
“…The importance of B cells for the development of type 1 diabetes in NOD mice has become increasingly evident over the last 10 years [1][2][3][4][5][6]. Several reports have demonstrated that eliminating B cells protects against type 1 diabetes in mice [1,3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of B cells for the development of type 1 diabetes in NOD mice has become increasingly evident over the last 10 years [1][2][3][4][5][6]. Several reports have demonstrated that eliminating B cells protects against type 1 diabetes in mice [1,3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated that eliminating B cells protects against type 1 diabetes in mice [1,3,6]. B1 cells moreover produce natural antibodies and recognise common bacterial antigens as well as self-antigens [7].…”
Section: Introductionmentioning
confidence: 99%
“…Given their role in producing pathogenic antibodies, especially in rheumatic diseases and systemic lupus erythematosus (SLE) [3,4], B lymphocytes have been targeted for immunomodulation by therapeutic depletion and other methods [5][6][7][8]. The involvement of B lymphocytes in type 1 diabetes mellitus (T1D) aetiopathogenesis was shown initially in the non-obese diabetic (NOD) mouse strain, where B lymphocyte-deficient mice or those treated with anti-immunoglobulin (Ig)M antibodies were protected significantly from disease [9,10]. In T1D, which is a T cell-driven autoimmune disease targeting the insulin-producing beta cells of the pancreatic islets of Langerhans, the pathogenic role of B lymphocytes has rested so far largely in their ability to act as antigenpresenting cells [11][12][13][14][15][16], producers of autoreactive antibodies [17,18] and modulators of the type of T cells that enter and are active within the pancreatic and islet environment [19].…”
Section: Introductionmentioning
confidence: 99%
“…B cells must be present for disease to occur in the NOD model (32)(33)(34), must have autoreactive specificities (35,36), must express appropriate MHCII alleles (37), and are essential for the processing and presentation of at least one islet Ag (38). Thus, a key role for B cells is most likely that of Ag presentation (39,40), which requires an organized lymphoid setting to promote T-B cell interactions.…”
mentioning
confidence: 99%